Early treatment of congenital syngnathia. A case report - Eduardo Alfredo Duro; Stella Maris Benitez; Albano del Cristo Barreto Paternina (Hygeia Press di Corridori Marinella, 2018)
Congenital syngnathia is a rare malformation. The synechia or synostosis of the maxilla and the mandible may be partial or complete and also be associated with other malformations. The syngnathia can be developed between the upper and lower alveolar ridges with a wide spectrum and range of severity documented in case reports. The authors report a newborn with complete syngnathia and discuss the management during the first days of life. Our goal is to help attending physicians understand anatomic and functional implications of syngnathia, and become familiar with strategies used in the early caring of a newborn with congenital syngnathia. Literature reveals results of different patients with poorly documented follow-up and different management. The priority is a safe airway and early nutrition with human milk to avoid the risk of aspiration pneumonia, malnutrition, and poor growth.